The governance of the special autonomy fund in improving welfare in special region of Yogyakarta / Harsono Dwi, Yuanjaya Pandhu and Winarni Fransisca - Dwi, Harsono; Pandhu, Yuanjaya; Fransisca, Winarni (2021)
Inequality in the welfare of the Indonesian people is an unresolved problem. This inequality is mainly reflected in the Gini index which is stagnant with an average of 0.39 in 2015-March 2020 (BPS, 2020). The impact of the COVID-19 pandemic has certainly increased inequality in welfare (Shidiq, 2020). The contribution of inequality in welfare can be seen in the poverty rate which is still high in Indonesia. The poverty rate is still high, at 25.14 million people or 9.22 percent of the total population (BPS, 2019). The magnitude of the poverty rate in Indonesia is also the cause of inequality which is still high at 0.38 in 2019 (BPS, 2019). Poverty directly affects welfare which affects the fulfillment of basic needs in society (Sen, 1981), and further creates social vulnerability (Kakwani and Silber, 2008; Ellis, 1984). Moreover, the World Bank (2019) estimates that 20.19 percent of Indonesia's population is in the poverty line, vulnerable to falling back below the poverty line if inflation and economic stabilization are not maintained. The COVID-19 pandemic, which has infected more than 1 million people until early 2021, will certainly accelerate the return of vulnerable Indonesians to being below the poverty line. This research focuses on the Special Region of Yogyakarta (DIY). DIY has the highest welfare inequality problem in Indonesia. BPS (2020) reported that in DIY the Gini index surpassed the national level, namely at 4.36. The poverty rate in DIY also reflects the same thing, amounting to 11.53 percent or 326.13 of the population (BPS, 2020). This figure has not been added to the population who are at the poverty line of 321,056 people and the severity of poverty is at 0.43 or twice the national figure (BPS, 2020). The condition of welfare inequality in DIY, especially poverty, is of course quite contradictory considering that DIY is the area with the second-highest national Human Development Index (HDI) (figure 79.97), far exceeding the national average of 60.44 (BPS, 2020).